Meningkatkan Kemampuan Bicara Berbahasa Inggris Mahasiswa Dalam Mendeskripsikan Suatu Kegiatan Dengan Menggunakan Model Pembelajaran Presentation Practice Produce (PPP) - Depi Prihamdani (Jurnal Sekolah Dasar, 2020)
The purpose of this study is to answer the problem of how to improve the English speaking ability of students who are not majoring in English at the University of Karawang Buana Struggle in general and in class in particular. specifically this study has a goal, namely: 1. Knowing the factors that affect students' ability to speak English. 2. Knowing the effectiveness of the application of learning, presentation, practice and produce learning models in improving students' speaking skills in English? 3. Knowing whether the application of the learning model of presentation, practice, produce can improve students' speaking skills in describing something using English. The research method used is descriptive qualitative. The steps taken in this study; 1. Determine the sample of the population (affordable), students who are not majoring in English at the University of Karawang Buana Struggle. 2. The predetermined sample is given a pre-test of speaking ability to find out their initial ability (they are asked to tell an object based on the picture given). 3. After the pre-test results are obtained, learning is done using the presentation practice produce (PPP) method. 4. Then the test is done to see the learning outcomes using the method.